Chlorination Enabling a Low‐Cost Benzodithiophene‐Based Wide‐Bandgap Donor Polymer with an Efficiency of over 17%. Issue 4 (10th December 2021) - Wang, Hang; Lu, Hao; Chen, Ya‐Nan; Ran, Guangliu; Zhang, Andong; Li, Dawei; Yu, Na; Zhang, Zhe; Liu, Yahui; Xu, Xinjun; Zhang, Wenkai; Bao, Qinye; et al.
Abstract: Three regioregular benzodithiophene‐based donor–donor (D–D)‐type polymers (PBDTT, PBDTT1Cl, and PBDTT2Cl) are designed, synthesized, and used as donor materials in organic solar cells (OSCs). Because of the weak intramolecular charge‐transfer effect, these polymers exhibit large optical bandgaps (>2.0 eV). Among these three polymers, PBDTT1Cl exhibits more ordered and closer molecular stacking, and its devices demonstrate higher and more balanced charge mobilities and a longer charge‐separated state lifetime. As a result of these comprehensive benefits, PBDTT1Cl‐based OSCs give a very impressive power conversion efficiency (PCE) of 17.10% with a low nonradiative energy loss (0.19 eV). Moreover, PBDTT1Cl also possesses a low figure‐of‐merit value and good universality to match with different acceptors. This work provides a simply and efficient strategy to design low‐cost high‐performance polymer donor materials. Abstract : Three D–D type wide‐bandgap donor polymers (PBDTT, PBDTT1Cl, and PBDTT2Cl) are designed and facilely synthesized. Organic solar cells (OSCs) based on PBDTT1Cl exhibit a high power conversion efficiency of 17% and a low nonradiative energy loss of 0.19 eV. In addition, PBDTT1Cl has a very low figure‐of‐merit and good universality, indicating its potential as a low‐cost polymer donor for high‐performance OSCs.